A new ctenochasmatid (Pterosauria, Pterodactyloidea) from the late Jurassic of Uruguay. (November 2021) - Soto, Matías; Montenegro, Felipe; Toriño, Pablo; Mesa, Valeria; Perea, Daniel
Abstract: A new ctenochasmatid pterosaur from the Tacuarembó Formation (Late Jurassic of Uruguay), Tacuadactylus luciae gen. et sp. nov. is described, based on a rostrum fragment with spatulated tip and dentary fragments. It closely resembles Gnathosaurus in the orientation of the teeth and the presence of interalveolar concavities. However, a unique combination of synapomorphies distinguishes it from other members of the Ctenochasmatidae. These include the presence of a spoon-shaped spatula not sharply demarcated from the post-spatula rostrum, teeth set in alveoli with raised alveolar borders and deep interalveolar concavities, teeth both anteriorly (i.e. procumbent) and laterally oriented, tooth density of 1.58–2 teeth/cm, tooth separation subequal to tooth size, absence of dorsal concavity, presence of a conspicuous system of vessels and foramina at least in the ventral part of the snout, teeth with veined sub millimetric texture of the enamel and unconspicuous carinae. In a phylogenetic analysis, the new taxon was retrieved as a gnathosaurine closely related to Gnathosaurus . The Tithonian-Berriasian biochron of the latter is coherent with the Late Jurassic age of the Batoví Member, as suggested by conchostracans and theropod teeth. This is one of the few South American Jurassic pterosaur taxa named so far and the oldest ctenochasmatid in this continent. As in Plataleorhynchus and Lonchodraco, Tacuadactylus luciae gen. et sp. nov. shows features that can be correlated with tactile foraging. Highlights: A new taxon of ctenochasmatid pterosaur is erected, Tacuadactylus luciae gen. et sp. nov. Is shows a spoon-shaped spatula and closely packed anterolaterally directed teeth. A phylogenetic analysis retrieve it as a gnathosaurine closely related to Gnathosaurus. It is the oldest ctenochasmatid in South America.